1988
DOI: 10.1007/bf02577004
|View full text |Cite
|
Sign up to set email alerts
|

Arterial anatomy and arteriographic diagnosis of arteriogenic impotence

Abstract: Abstract.One hundred twenty-six bilateral selective arteriographic examinations of the iliopudendal vascular tree were performed after comprehensive multidisciplinary evaluation in patients with chronic erectile dysfunction. Best imaging results were obtained by performing the arteriography under epidural anesthesia after intracavernous injection of a vasoactive drug combination. The arteriography is mandatory prior to revascularization procedures. It is further indicated in primary erectile dysfunction and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Virag et al 22 found a 67.8% prevalence of arteriographic abnormalities in the four main blood vessels of the penis in patients in whom organic ED had been established, of whom 86% were smokers. Bahren et al 56 found that 82% of their subjects with arteriographically proved peripheral arteriosclerotic lesions were heavy smokers. In a similar study, Rosen et al 57 found smoking to be a significant independent risk factor for atherosclerotic lesions in the internal pudendal and common penile arteries.…”
Section: Effects On Penile Blood Flowmentioning
confidence: 98%
“…Virag et al 22 found a 67.8% prevalence of arteriographic abnormalities in the four main blood vessels of the penis in patients in whom organic ED had been established, of whom 86% were smokers. Bahren et al 56 found that 82% of their subjects with arteriographically proved peripheral arteriosclerotic lesions were heavy smokers. In a similar study, Rosen et al 57 found smoking to be a significant independent risk factor for atherosclerotic lesions in the internal pudendal and common penile arteries.…”
Section: Effects On Penile Blood Flowmentioning
confidence: 98%
“…The penile arterial supply displays slight variation in its anatomy [4,5]. The penis is usually supplied by branches of the internal pudendal artery, which continue as the penile artery.…”
Section: Penile Anatomymentioning
confidence: 99%
“…The solitary ventrally located corpus spongiosum is enclosed by a thinner layer of tunica albuginea and surrounds the penile urethra. The spongiosum is anatomically independent of the cavernosa.The three corpora are enclosed by the more superficial Buck's fascia.The penile arterial supply displays slight variation in its anatomy [4,5]. The penis is usually supplied by branches of the internal pudendal artery, which continue as the penile artery.…”
mentioning
confidence: 99%
“…For example, the common penile artery may arise from the terminus of the internal pudendal artery or from an accessory pudendal artery. Also, unilateral absence or hypoplasia of a dorsal artery has been shown in up to 30% of potent volunteers in a series by Bahren et al 13 It is this variability in penile arterial anatomy that leads to frequent misinterpretations of duplex ultrasonography, and therefore, pudendal arteriography remains the current gold standard for penile arterial evaluation.…”
Section: Duplex Ultrasonographymentioning
confidence: 99%